ANALYSIS OF THE INFLUENCE OF GENERATION, GENDER, FUTURE PERSPECTIVE, FINANCIAL RISK TOLERANCE, AND FINANCIAL LITERACY ON FINANCIAL PLANNING FOR THE RETIREMENT OF STATE CIVIL APPARATUS - Ruth Jelita Silaban; Khaira Amalia Fachrudin; Fahmi Natigor Nasution (CV. Radja Publika, 2024)
This research is a quantitative study that aims to examine the influence of demographics (gender and generation), psychological factors (future perspective, financial risk tolerance, and clarity of retirement goals), and financial literacy on financial planning for retirement. The population in this study were state civil servants in the vertical unit of one of the ministries in the North Sumatra region, Indonesia. The sample in this study was 123 employees who were carried out using a non-probability sampling method and selected randomly. Data collection was carried out by distributing questionnaires via Google-form media. The data analysis technique uses the Structural Equation Model (SEM) analysis method based on Partial Least Square (PLS). The results of this research show that generation, future perspective, clarity of retirement goals, and financial literacy have a positive and significant effect on financial planning for retirement. Meanwhile, gender and financial risk tolerance do not have a significant effect on financial planning for retirement.